Examining Chen and Starosta’s model of intercultural sensitivity in a multiracial collectivistic country. - Tamam, Ezhar (World Communication Association, 2010)
This study examines the applicability of Chen and Starosta’s model of intercultural sensitivity in Malaysian culture using university student samples. A total of 447 randomly selected undergraduate students of a multicultural public university completed self-administered questionnaires. The study could not reproduce the five-factor structure formulated by Chen and Starosta. Instead, a three-factor structure (interaction attentiveness and respect, interaction openness, and interaction confidence) is devised from 21 items of Chen and Starosta’s instrument for further theoretical and measurement validation.